Vertical Upflow Convective Boiling: Flow Regimes, Heat Transfer and EHD Augmentation - ERAGHUBI, MUNIR (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2018)
This work focuses on vertical upflow convective boiling in a tubular heat exchanger. The work is experimental and utilizes a novel transparent sapphire test section coated with a transparent film of ITO. This allows simultaneous heating of the working fluid, measurement of the local heat transfer coefficient and visualization of the two phase flow. The work first considers vertical upflow convective boiling in a straight open tube in order to establish a baseline understanding of the configuration. The study then considers the influence of EHD on the two phase flow and heat transfer. The experiments were performed using HFE7000 as the working fluid, an inlet pressure or 1.2 bars, inlet subcooling of 2?C and mass flux ranging between 50 and 300 kg/(m2 s). Flow regimes for various mass and heat fluxes have been visualized along the test section using high speed videography. Three main flow patterns have been observed under different mass and heat fluxes: bubbly flow, bubbly-slug flow and churn flow. The measured boiling conditions were plotted on seven existing vertical flow pattern maps and the agreement discussed. The heat transfer tests were performed by fixing the flow rate and progressively increasing the heat flux prior to reaching the critical heat flux. A second set of identical tests were performed with a 3 mm diameter stainless steel rod positioned concentrically inside the tube to test the influence of moderate confinement. It has been found that once fully developed boiling conditions are achieved, the heat transfer is generally insensitive to the flow rate and moderate confinement. Seven well-established forced boiling heat transfer correlations have been applied to predict the heat transfer coefficient and the accuracy of these are discussed. In the final phase of this study, EHD augmentation of the flow and heat transfer for vertical upflow convective boiling was investigated. To the best of knowledge, this is the first study of vertical upflow boiling with EHD augmentation that included local heat transfer measurements with detailed visualization of the flow regimes and phase interactions. One very striking conclusion is that, for the bubbly flow regime considered, there is very strong electrophoretic interaction with the phases, and this is not what has been observed for horizontal flows where liquid extraction (dielectrophoretic) dominates the EHD effect. The electrophoretic force interaction is clear from the fact that bubbles are attracted to the electrode, which is in the opposite direction of the dielectrophoretic forces, and for higher AC frequencies the bubbles zigzag at the frequency of the applied voltage, where the dielectrophoretic force would respond at double this frequency. The repercussion of this new finding is not only relevant for vertical two phase flows, but also for microgravity convective boiling since they will have generally similar flow regimes as those considered here.
APPROVED
Keywords: Vertical Upflow; Convective Boiling; Flow Regimes; Heat Transfer; Electrohydrodynamics